Control of magnetic particles in centrifugal microfludic platforms / Sogol Givehchi - Sogol , Givehchi (2014)
Centrifugal microfluidic platforms, also known as CD-like microfluidics, are types of lab-on-a-chip devices that employ centrifugal force to pump liquid between micro chambers via micro channels. Magnetic particles can be used in centrifugal microfluidic platforms for bimolecular assays such as the enzyme-linked immune sorbent assay (ELISA), polymer chain reaction (PCR) and other applications. Magnetic particles can act as mobile solid supports for bio reactions due to their specific surface functionalization. For this reason, trapping, transport and detection of magnetic particles are very important operations in centrifugal microfluidic platforms for research applications and clinical diagnostics. Magnetic forces are required for controlling the magnetic particles in CD-like microfluidic devices. Therefore, external magnetic field should be applied on micro chambers. In previous studies, external magnetic field was generated by means of sophisticated coil arrays that require skillful technicians and permanent magnets which need manual tedious procedures. In addition, other studies attempted to manipulate magnetic particle when CD is in stationary state. This study introduces a novel electromagnetic platform that allows controlling of magnetics particles movements on CD-like microfluidics during rotational CD automatically. The required magnetic force to move magnetic particles under a centrifugal force are estimated by MATLAB software. By employing the magnetic force equation and based on the required magnetic force, the exact value of required magnetic flux density at the location of magnetic particles was calculated. Then, an electromagnetic platform which produces required magnetic flux density was designed using COMSOL simulation software. Our results indicate that the designed electromagnetic platform with 16 solenoids inside the ring-shaped core is able to generate the required magnetic flux density (more than 1.91 T).By utilizing the electromagnetic platform in this project, magnetic particles can be trapped in one chamber for 10 second and then can be transported from one chamber to another chamber automatically. This preliminary result will lead to the future development of electromagnetic platforms and implementation of fully automated biomedical assays in centrifugal microfluidic applications.